2015
DOI: 10.1021/acs.organomet.5b00065
|View full text |Cite
|
Sign up to set email alerts
|

Phospha Derivatives of Tris(2-aminoethyl)amine (tren) and Tris(3-aminopropyl)amine (trpn): Synthesis and Complexation Studies with Group 4 Metals

Abstract: The N,N′,N″-triphenyl-substituted derivative of tris(2-aminoethyl)phosphine (Ph 3 -phospha-tren, P-(CH 2 CH 2 NHR) 3 , R = Ph) and four derivatives of the related t r i s ( 3 -a m i n o p r o p y l ) p h o s p h i n e ( p h o s p h at r p n , P-(CH 2 CH 2 CH 2 NHR) 3 , R = i Pr, t Bu, Si t BuMe 2 , Ph) have been synthesized in addition to the parent phospha-trpn. Out of these ligand systems, only the N,N′,N″-triphenyl-substituted phosphatrpn derivative P(CH 2 CH 2 CH 2 NHPh) 3 was found to be suitable for coor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 62 publications
1
21
0
Order By: Relevance
“…In agreement with the above mentioned expectation, the propylene-and benzylene-linked ligands, pr [NPN]H 2 and bn [NPN] H 2 , were readily synthesised following an adaption of our previously reported experimental procedure for the preparation of related triamidophosphine scaffolds (see Scheme S1 in the ESI †). 58,59 Both ligands were obtained in gram quantities and high purities, which allowed for their direct use to prepare the envisioned group 4 complexes shown in Chart 2.…”
Section: And Bn [Npn]hmentioning
confidence: 99%
“…In agreement with the above mentioned expectation, the propylene-and benzylene-linked ligands, pr [NPN]H 2 and bn [NPN] H 2 , were readily synthesised following an adaption of our previously reported experimental procedure for the preparation of related triamidophosphine scaffolds (see Scheme S1 in the ESI †). 58,59 Both ligands were obtained in gram quantities and high purities, which allowed for their direct use to prepare the envisioned group 4 complexes shown in Chart 2.…”
Section: And Bn [Npn]hmentioning
confidence: 99%
“…21 Tris(2-aminoethyl) amine (TREN), a flexible C 3 symmetric linker, has been extensively utilized in co-ordination chemistry as tri-or tetradentate ligand for various metal ion interactions and sensor based applications. [22][23][24][25] It has been reported that the flexibility of TREN assisted in self-assembly of the collagen mimetic scaffold due to effective adjusting of the three peptide chains to form triple helical packing. 26 The TREN binding site in the artificial L-serine derivative based metallocatalyts has been reported to act as allosteric regulation sites due to conformation change upon metal binding.…”
mentioning
confidence: 99%
“…That nitrido complexes (XylN t Bu) 3 Mo≡N and Mes 3 Mo≡N of Cummins et al and Floriani et al, which both lack trans ‐donor functionality, were found to be catalytically inactive is in line with this argument. With the two phospha‐ tren ligands P(CH 2 CH 2 NHR) 3 (R = SiMe 3 , Ph) reported to date, however, no well‐defined metal complexes have been isolated . Therefore, closely related systems have been targeted over the past years, and the N , N′ , N′′ ‐triaryl‐substituted methylene‐linked triaminophosphanes P(CH 2 NHR) 3 (R = Ph, Xyl, C 6 F 5 ) were recently shown to react productively with (Me 2 N) 3 Mo≡N .…”
Section: Introductionmentioning
confidence: 99%